Relating gastric scintigraphy and symptoms to motility capsule transit and pressure findings in suspected gastroparesis. Issue 2 (5th September 2017) - Hasler, W. L.; May, K. P.; Wilson, L. A.; Van Natta, M.; Parkman, H. P.; Pasricha, P. J.; Koch, K. L.; Abell, T. L.; McCallum, R. W.; Nguyen, L. A.; Snape, W. J.; Sarosiek, I.; et al.
Abstract: Background: Wireless motility capsule (WMC) findings are incompletely defined in suspected gastroparesis. We aimed to characterize regional WMC transit and contractility in relation to scintigraphy, etiology, and symptoms in patients undergoing gastric emptying testing. Methods: A total of 209 patients with gastroparesis symptoms at NIDDK Gastroparesis Consortium centers underwent gastric scintigraphy and WMCs on separate days to measure regional transit and contractility. Validated questionnaires quantified symptoms. Key Results: Solid scintigraphy and liquid scintigraphy were delayed in 68.8% and 34.8% of patients; WMC gastric emptying times (GET) were delayed in 40.3% and showed 52.8% agreement with scintigraphy; 15.5% and 33.5% had delayed small bowel (SBTT) and colon transit (CTT) times. Transit was delayed in ≥2 regions in 23.3%. Rapid transit was rarely observed. Diabetics had slower GET but more rapid SBTT versus idiopathics ( P ≤ .02). GET delays related to greater scintigraphic retention, slower SBTT, and fewer gastric contractions ( P ≤ .04). Overall gastroparesis symptoms and nausea/vomiting, early satiety/fullness, bloating/distention, and upper abdominal pain subscores showed no relation to WMC transit. Upper and lower abdominal pain scores ( P ≤ .03) were greater with increased colon contractions. Constipation correlated with slower CTT and higher colon contractions ( P = .03). Diarrhea scores were higher with delayed SBTT and CTT ( P ≤ .04). Conclusions & Inferences: Wireless motility capsules define gastric emptying delays similar but not identical to scintigraphy that are more severe in diabetics and relate to reduced gastric contractility. Extragastric transit delays occur in >40% with suspected gastroparesis. Gastroparesis symptoms show little association with WMC profiles, although lower symptoms relate to small bowel or colon abnormalities. Abstract : Wireless motility capsule (WMC) findings in suspected gastroparesis and relations to symptoms have been poorly defined. Evaluation of patients with gastroparesis symptoms revealed gastric emptying delays with WMCs that were similar to scintigraphy, were related to reduced contractility, and were often associated with extragastric or generalized transit delays; symptoms correlated poorly with WMC profiles. These findings provide insight into motor abnormalities in gastroparesis pathogenesis and form a basis for future investigations studying the impact of WMC testing on clinical care.